A review of the geology of primary tin deposits with emphasis on the factors that control grade and tonnage - Archer, Paul D (Rhodes University, Faculty of Science, Department of Geology, 1981)
"The purpose of this dissertation is ... to review the economic geology of primary tin deposits and the geological factors that control grade and tonnage . The work concludes with a discussian of the implications of these geological controls on evaluation"-- Introd., p. 1
Keywords: Tin ores; Granite; Geology; Tonnage